CHILDREN’S DIFFERENCE SEQUALITY EXPRESSION IN PEDAGOGY ON THE BASIS OF EGALITARISM CONTEXT - Juodaitytė, Audronė (Acta Paedagogica Vilnensia, 2011)
Suggestive egalitarianism has a long history within educational system, i.e. one of the first ideologists would be J. J. Rousseau. Suggestive egalitarianism thesis arises in European democracy thought and becomes a new sphere of social philosophy and epistemology while a child’s being different is an educational virtue.In this paper the concept of children’s difference equality on the basis of suggestive egalitarianism is revealed. The socio-cultural meanings’ interpretations are set as well based on European democratic thought paradigm. The scientific positions contextualizing those interpretations are analyzed. Specifically theses: “children’s difference equality”, “children’s equality”, and „children communities’ equality”. These pedagogic streams and social movements that empower children’s equality expression are identified. Educational situations are interpreted as well, especially these were educational relations’, “child–adult” socio-cultural meaning is seen. Problematic questions for scientific and practical discussions are formulated.
Keywords: suggestive egalitarianism; children’s difference equality; and equality empowerment